Self-regulated learning strategies as predictors of senior secondary school students’ chemistry achievement in Ondo State, Nigeria (2017)
The study investigated on self- regulated learning strategies as predictors of Chemistry students’ attitude to Chemistry in senior secondary schools in Ondo State. The research adopted survey research design. 400 students were used for the research work which was drawn randomly using simple random sampling technique. The research instruments for the study were SRLS questionnaire containing 10 items on each of the component and students’ attitude to Chemistry (SATC) questionnaire with 25 items. The validity of the instruments was assessed and found to be adequate by the experts. Crobanch alpha was used to determine the reliability of SRLS with a coefficient of 0.86, 0.89, 0.85 and 0.96 and 0.78 for (SATC) at 0.05 level of significance. The data collected was analysed using descriptive and inferential statistics such as: mean standard deviation, Pearson Product Moment Correlation and Analysis of Variance. The study revealed that there was significant relationship between goal setting (r = 0.063; P>0.05) and students’ achievement in Chemistry. Self- monitoring (r = 0.025; P<0.05), self- evaluation (r = 0.012; P<0.05) and self-efficacy (r = 0.064; P<0.05) had significant relationship with students' achievement in Chemistry. The result also revealed that there was no composite contribution of SRLS on students’ achievement in Chemistry (F(4,395) = 0.673; P>0.05). None of the independent variables predicts students’ achievement in Chemistry. Based on the findings it was recommended that students should be encouraged to develop enough self-regulated learning strategies that will facilitates their learning while Government should supply new materials like Chemistry textbooks so that students would be exposed to more facts about Chemistry and teachers on their part should improve themselves academically whenever such opportunity are available so that they can get better.